Effects of orthopedic treatment on temporomandibular joint in class III patients with anterior crossbite: a literature review. - Moscoso Sivirichi, Karen (2023)
Objective: The study aimed to evaluate the effects of orthopedic treatment on the temporomandibular joint (TMJ) in class III patients with anterior crossbite. Materials and Method: Four databases were reviewed until December 2022 (Scopus, PubMed, Embase, and Science Direct). Two independent reviewers selected studies reporting TMJ changes and the presence of TMJ dysfunction in Class III patients with anterior crossbite who received orthopedic treatment. The methodological quality of the studies was analyzed using the PRISMA checklist. Results: Twelve articles were selected for the study after a detailed search according to the selection criteria. Post-treatment studies demonstrated a low prevalence of TMJ pain after using the Delaire face mask, chin rest, modified Jasper Jumper, and fixed reverse Twin block. After treatment with reverse Twin block, an increase in condylar volume and joint spaces (p<0.001) was observed, followed by a significant decrease in posterosuperior joint spaces (p<0.001). Conclusions: Not enough evidence has been found to determine the presence of TMD or TMJ changes after using orthopedic devices for anterior crossbite correction.